Los rincones didácticos: espacios efectivos para mejorar la lectura en el sexto grado de Educación General Básica - Cumbicus Espinoza, Lizbeth Carolina (2023)
The research titled “DIDACTIC CORNERS”: effective spaces to improve reading, has the general objective of determining the influence of didactic corners into the improvement of reading in the sixth grade of the "Alonso de Mercadillo" School during the Academic Period 2022-2023. To carry out this study, a type of descriptive research was used, with a mixed approach and quasi-experimental design; in this process the following methods were applied: scientific, descriptive, analytical, synthetic, inductive, deductive and statistical; The techniques that were used were: interview, pre-evaluation and post-evaluation, in the same way the instruments used were: interview questionnaire, pre-evaluative and post-evaluative questionnaire, these contributed significantly in data collection , to obtain information, the teacher was interviewed and a diagnostic evaluation was applied to the students, which allowed diagnosing the reading level of the students. The investigated population includes a teacher and thirty-seven children. The results allow us to determine that 14% of the investigated students have an inferential reading level, 51% a literal reading level, 23% a low reading level and the other 11% a very low level. To support the improvement of reading in children, a guide of didactic activities called "Traveling with imagination" was designed and applied; According to the results obtained, teachers are encouraged to use strategies designed to the improvement of the reading through the “DIDACTIC CORNERS”. Keywords: Didactic corners, reading levels, strategies, didactic activities, teaching-learning.